Adsorbate interactions on the GaN(0001) surface and their effect on diffusion barriers and growth morphology. Issue 3 (3rd January 2017) - Chugh, Manjusha; Ranganathan, Madhav
Abstract : Reduced diffusion barriers of N adatoms around Ga adatoms lead to better surface morphology during epitaxial GaN(0001) growth. Abstract : Studying the adsorbate interactions on a surface helps in understanding the growing surface morphologies and calculating the effective surface diffusion barriers. We study the interaction between Ga–Ga, N–N and Ga–N adatom pairs on the polar GaN(0001) surface using ab initio calculations based on density functional theory. The interaction energy between two adatoms on the surface does not seem to follow definite trends with increasing distance between the adatoms. The presence of a number of possible reconstructions on clean GaN(0001) and periodic effects due to the finite size complicate the analysis of the interactions. Various components of the total interaction energy are separated. We find that there is a large substrate lattice distortion caused due to Ga and N adatoms. The resulting elastic interaction is a major component of the interactions between the adatoms on the GaN(0001) surface. The dipolar interaction is much smaller in magnitude. We also evaluate the component of the interaction energy due to the substrate-mediated electronic interactions. The barriers for surface hopping of adatoms are significantly modified in the presence of other adatoms. We identify several possible surface hopping processes for Ga and N adatoms and calculate their barriers. In particular, we find that the N adatom has a lower barrier to move to an adjoining site on the other side of a neighboring Ga adatom. Kinetic Monte Carlo simulations are performed to see the effect of adatom interactions on the growing surface morphologies of GaN(0001). At the submonolayer growth stage, the fast diffusion of N adatoms located near Ga adatoms leads to more regular island features. In this way, we illustrate the role of adatom interactions in the initial surface nucleation and the morphologies of the growing GaN(0001) film.